Amalgam versus resin composite for the restoration of posterior teeth: disparities between public clinical practice and dental education in southern Brazil - Clarissa Fatturi Parolo; Aline Macarevich; Juliana Jobim Jardim; Marisa Maltz (Universidade Federal do Rio Grande do Sul. Faculdade de Odontologia, 2011)
Purpose: To compare the restorative material used in the treatment of posterior teeth taught and performed in two Dental Schools (UFRGS and ULBRA) and in 8 basic health units (BHU) from the Public Health System in Porto Alegre, Brazil. Materials and methods: Data referring the teaching of restorative procedures using amalgam (AM) or resin (R) were obtained through the analysis of patient's files and questionnaires applied to final year dental students. Information regarding restorative procedures at BHU was obtained through patient's records and a questionnaire applied to the dentists. The type of restorative material used in both BHU and Dental Schools were compared by chi-square test. Results: At UFRGS, 327 restorations were performed, 78.28% R and 21.72% AM, and at ULBRA 366 restorations, 92.63% R and 7.37% AM. At BHU, 1664 restorations were performed (35.93% R and 64.07% AM). A major proportion of AM restorations was performed in the Public Health Service in comparison to both Dental Schools, in which resin restorations prevailed (p=0.000). Conclusion: The change from AM to R in the dental material choice for posterior teeth at Dental Schools was not followed by the Public Health System, where the AM is still widely used in posterior teeth.